Respuesta :

Answer:

At x = 4 ⇒ g(x) = f(2)

Step-by-step explanation:

* In the functions f(x) = 3x - 1 and g(x) = 2x - 3, the domain is

  the values of  x and the range is the values of y

∵ g(x) = f(2)

* Then you will use the range of f(x) at x = 2 to find the domain of g(x)

∵ The domain of f(x) = 2

∵ f(x) = 3x - 1

∴ f(2) = 3(2) - 1 = 6 - 1 = 5

* The range of f(x) = 5

∵ f(2) = g(x)

∴ 5 = g(x)

∵ g(x) = 2x - 3

∴ 2x - 3 = 5 ⇒ add 3 to both sides

∴ 2x = 8 ⇒ divide both sides by 2

∴ x = 4

* At x = 4 ⇒ g(x) = f(2)